361 A randomised open-label phase I/II study adding ONCOS-102 to pemetrexed/cisplatin in patients with unresectable malignant pleural mesothelioma – 12 month analysis of biomarkers and clinical outcomes. (10th December 2020) - Jaderberg, Magnus; Cedres, Susana; Paz-Ares, Luis; Serres, Xavier; Ricordel, Charles; Isambert, Nicolas; Aix, Santiago Ponce; Levitsky, Victor; Kuryk, Lukasz; Moller, Anne-Sophie; Vetrhus, Sylvia
Abstract : Background: Malignant pleural mesothelioma (MPM) is a rare, aggressive malignancy without curative treatment. Majority of patients receive pemetrexed/cisplatin as standard of care (SoC). Median overall survival in unresectable disease is 12 months. ONCOS-102 is a granulocyte-macrophage colony stimulating factor (GM-CSF) expressing oncolytic adenovirus (Ad5/3-D24-GMCSF) with a unique ability to both prime and boost immune responses. The aim of the study was to assess immune and clinical responses as well as safety in patients with 1st and 2nd line unresectable MPM. Methods: Eligible patients (experimental arm, n=20) received ONCOS-102 given intratumorally under CT or US guidance at a dose of 3 × 10 × 11 on Day 1, 4, 8, 36, 78 and 120 plus six cycles of SoC starting on Day 22. The control group (n=11) received only SoC. Imaging was done at baseline, Day 43–64 and 127–148. Patients were monitored regularly for immunological assessment including lesional biopsies (baseline and Day 36). Primary objective was safety and tolerability. Secondary objectives were immunological activation, ORR, PFS and OS as well as correlation between immunological activation and clinical outcome. Results: There were no safety concerns nor DLTs. In 1st line patients ORR/DCR was 30%/90% in the experimental group and 33%/83% in the control group. 2nd line patients had ORR/DCR of 11%/67% in the experimental group and 60%/80% in the control group. 12-month survival rate for the 1st line pts was 64% in the experimental group and 50% in the control group. PFS and OS are still to be reported. The treatment with ONCOS-102 induced strong upregulation of multiple genes associated with immune activation in tumor lesions. Profound innate and adaptive immune activation was observed in the experimental vs control group that was associated with better clinical outcome. In addition to an increase in intra-tumoral cytotoxic T-cells (10/15 pts), the treatment with ONCOS-102 resulted in polarization from M2 to M1 macrophages. An upregulation of PD-L1 was reported in 9/15 pts in the experimental group vs 2/5 pts in the control arm, highlighting the potential of ONCOS-102 as an immunosensitizing agent for combinatory therapies with checkpoint inhibitors. Conclusions: ONCOS-102 treated patients benefited from superior immune activation compared to patients receiving SoC with preliminary signals of clinical efficacy. Upregulation of adaptive immunity and cytotoxicity related gene expression, PD-L1 level and M2 to M1 macrophage polarization indicate that ONCOS-102 can induce a favourable TME modulation thus providing a scientific rationale for combination with check point inhibition. Trial Registration: ClinicalTrials. gov NCT02879669 Ethics Approval: This study was approved by the IRBs of all the sites in Madrid, Barcelona, Rennes and Poitiers.